Contracaecum osculatum (Rudolphi, 1802) Baylis 1920 - Arai, Hisao P.; Smith, John W. (Zenodo, 2016)
* Contracaecum osculatum (Rudolphi, 1802) Baylis, 1920 ( sensu lato ) Includes: * C. osculatum A auct .; * C. osculatum B auct .; and * C. osculatum C auct . Description (after J. W. Smith & Wootten 1984c, and Moravec 2013). NB: the following description applies also to * Phocascaris sp. and/or * Contracaecum sp. (see below). Greenish brown in colour, sometimes tinged with red, L3 about 7 to 30 long, lying coiled in capsules of irregular shape (J. W. Smith & Wootten 1984c). Mouth, lips, boring tooth, and excretory pore similar to those of Anisakis simplex L3 (see Fig. 73 A,B,C). According to Moravec (2013), L3 are 3.81–22.00 long, maximum width 0.15–0.53. Oesophagus 0.55–1.71 long, ventricular appendix 0.54–1.58, and intestinal caecum 0.20–0.89. Single excretory cell extends posteriorly to mid- body region. Tail 0.09–0.21 long, narrows rapidly to a point lacking a mucron. Anterior and posterior ends of an L3 shown diagrammatically in Fig. 75 A,B. Sites: intestinal lumen, mesenteries, musculature, viscera Hosts: Boreogadus saida (13); Gadus macrocephalus (11); Gadus morhua (1, 4, 5, 7, 8, 9, 10, 14, 16); Glyptocephalus cynoglossus (1); Hippoglossoides platessoides (10); Hippoglossus hippoglossus (11); Mallotus villosus (10); Myoxocephalus scorpius (10); Oncorhynchus mykiss (6); Oncorhynchus tshawytscha (12); Pseudopleuronectes americanus (10); Theragra chalcogramma (11); Urophycis tenuis (5, 15); unspecified “fish” (2, 3) Distribution: Atlantic, Nunavut, Pacific Records: 1. McClelland et al. 1985 (AT); 2. Berland et al. 1989 (AT); 3. Burt et al. 1989a (AT); 4. Brattey et al. 1990 (AT); 5. McClelland et al. 1990 (AT); 6. J. W. Smith et al. 1990 (EX, AT); 7. Likely & Burt 1992 (AT); 8. Marcogliese & Boily 1994 (AT); 9. McClelland & Marcogliese 1994 (AT); 10. Brattey 1995 (AT); 11. Paggi et al. 1998 (PA); 12. Urawa et al. 1998 (PA); 13. Køie 2009 (NU); 14. Khan et al. 2011 (AT); 15. Melendy et al . 2005 (AT); 16. McClelland & Melendy 2011 (AT) Published as part of Arai, Hisao P. & ...